Differentiation of NG108-15 cells induced by the combined presence of dbcAMP and dexamethasone brings about the expression of N and P/Q types of calcium channels and the inhibitory influence of muscarinic receptors on calcium influx - Dolezal, V; Lisá, V; Diebler, M F; Kasparová, J; Tucek, S (Brain research, 2001)
Differentiation of cholinergic cell line NG108-15 induced by a combination of dibutyryl cyclic AMP (dbcAMP) and dexamethasone enhances the cholinergic phenotype of the cells more than that induced by either agent alone. We investigated the effect of treatment with dbcAMP and dexamethasone on potassium depolarization-evoked influx of calcium and its regulation by the muscarinic agonist carbachol. Depolarization of control cells and of cells differentiated in the presence of dbcAMP or dexamethasone alone, or in the combined presence of dbcAMP and dexamethasone induced, respectively, 2.2-, 4.3-, 2.7- and 10.7-fold increases of the resting [Ca(2+)](i). Dexamethasone alone and the combination of dbcAMP and dexamethasone augmented the number of muscarinic receptors by 25 and 40%, respectively. Inhibitors of N (omega-conotoxin GVIA) or P/Q (omega-agatoxin TK) calcium channels had no effect on Ca(2+) influx in control cells, whereas in cells differentiated in the combined presence of dbcAMP and dexamethasone they significantly diminished the influx of Ca(2+) by 20 and 5%, respectively. Carbachol attenuated calcium influx in differentiated cells in an atropine-insensitive manner if it was present during stimulation. This effect of carbachol was probably due to an open-channel block of L type channels. In the presence of nifedipine, carbachol attenuated the influx of Ca(2+) into cells differentiated with dbcAMP and dexamethasone by 20% in an atropine-sensitive way. Data show that differentiation of NG108-15 cells by dbcAMP and dexamethasone promotes the expression of functional nifedipine-insensitive N and P/Q types of Ca(2+) channels and that the nifedipine-insensitive calcium influx becomes subject to inhibitory regulation by muscarinic receptors.
Keywords: vápníková signalizace; Animals; Carbachol; dibutyryl cyklický AMP; membránové potenciály; Muscarinic Antagonists; lékové interakce; Tretinoin; Drug Interactions; vápníkové kanály - typ N; tretinoin; Nifedipine; buněčná diferenciace; karbachol; blokátory kalciových kanálů; lidé; nifedipin; Cholinergic Agonists; receptory muskarinové; vápník; antagonisté muskarinových receptorů; kultivované buňky; Calcium Channels, P-Type; Calcium Channels, N-Type; regulace genové exprese; Cells, Cultured; vápníkové kanály - typ P; cholinergní agonisté; Calcium; intracelulární tekutina; dexamethason; Calcium Channel Blockers; Intracellular Fluid; Receptors, Muscarinic; Calcium Signaling; Dexamethasone; Bucladesine; Cell Differentiation; Gene Expression Regulation; zvířata; Membrane Potentials; Humans